2008
DOI: 10.1242/dev.021949
|View full text |Cite
|
Sign up to set email alerts
|

Post-meiotic transcription inDrosophilatestes

Abstract: Post-meiotic transcription was accepted to be essentially absent from Drosophila spermatogenesis. We identify 24 Drosophila genes whose mRNAs are most abundant in elongating spermatids. By single-cyst quantitative RT-PCR, we demonstrate post-meiotic transcription of these genes. We conclude that transcription stops in Drosophila late primary spermatocytes, then is reactivated by two pathways for a few loci just before histone-to-transition protein-to-protamine chromatin remodelling in spermiogenesis. These mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
133
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 25 publications
(29 reference statements)
14
133
0
2
Order By: Relevance
“…For example, it is thus possible to perform RT-qPCR to analyze the transcriptional regulation of specific genes during defined stages of spermatogenesis, as has already been demonstrated 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is thus possible to perform RT-qPCR to analyze the transcriptional regulation of specific genes during defined stages of spermatogenesis, as has already been demonstrated 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila spermatogenesis, transcription ceases almost completely with entry into meiotic divisions. Thus, post-meiotic spermatogenesis is mainly based on translationally repressed and stored mRNAs synthesized in an extended meiotic prophase [13][14][15][16] . Therefore, tools like RNA interference or the use of non-conditional mutants are not suitable for studying specifically the post-meiotic roles of gene products that also fulfill essential functions in pre-meiotic or meiotic germ cell development.…”
Section: Introductionmentioning
confidence: 99%
“…It has been earlier considered that the transcription in spermatogenesis after meiosis is very low or completely absent [5,14,15]. Barreau et al (2008) used RT-PCR and in situ hybridization to demonstrate that 96% of the genes whose mRNAs are detectable in spermatids are transcribed in spermatocytes [16]. The remaining 4% of the genes are transcribed postmeiotically before the moment when protamines substitute for histones in the spermatid nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this and other similar studies, it has generally been accepted that the postmeiotic phase is devoid of transcriptional activity and led to the prevailing notion that proteins required later during the postmeiotic stages were translated from mRNAs produced during meiosis and stored in the cytoplasm (Schäfer et al 1995). Two contemporary studies have challenged this view, one using a targeted gene expression approach demonstrating mRNA accumulation in postmeiotic spermatids (Barreau et al 2008) and our recent microarray analysis estimating substantial genome-wide expression during postmeiosis (Vibranovski et al 2009). This latter study demonstrated that 20-30% of testis genes transcribed are over expressed during postmeiosis in comparison to meiosis.…”
mentioning
confidence: 99%